Recent advances in biochar-based adsorbents for CO2 capture - Guo, Shifang; Li, Yuqing; Wang, Yaru; Wang, Linna; Sun, Yifei; Liu, Lina (Carbon Capture Science & Technology, 2022)
The global industrialization accelerates the use of fossil fuels and hence the excessive emissions of greenhouse gasses, especially carbon dioxide (CO2), which poses a serious threat to the ecological environment. CO2 capture is considered as a potential strategy to reduce the amount of CO2 released into the atmosphere. The development of adsorption materials that are both economically feasible and effective is the most critical issue. Biochar is a promising candidate for CO2 capture among the capture materials. It offers a diverse range of raw materials and a lower environmental impact than other adsorbent materials. Even though pristine biochar could be employed directly to CO2 capture, it generally exhibits a poor adsorption performance. Therefore, biochar needs to be modified in practical applications to improve physicochemical properties such as specific surface area, pore structure, and surface functional groups. This paper summaries recent research advances in biochar-based adsorbents for CO2 adsorption. Pre-combustion capture technology and post-combustion capture technology are investigated. The production of biochar and the influence of raw materials and process conditions on the adsorption capacity of CO2 are described in detail. The mechanism of CO2 adsorption on biochar is also discussed, which summarized physical and chemical adsorption, respectively, as well as the corresponding presentation of some current methods of physical/chemical modification of biochar. Finally, the future prospects are proposed in order to provide a guideline for the adsorption of CO2 by biochar. Despite the progress made in the production of biochar for CO2 adsorption, more efforts are needed to produce biochar with higher adsorption capacity and long-term stability for large-scale CO2 capture.